Innovative uses of carbamoyl benzoic acids in coagulation-flocculation’s processes of wastewater - Martinez Quiroz, Marisela; López Maldonado, Eduardo Alberto; Ocho-Terán, Adrián; Oropeza-Guzmán, Mercedes T.; Pina-Luis, Georgina; Zeferino Ramírez, José (My University, 2017)
The use of carbamoyl benzoic, acids as separation new agents, to remove on the hazardous heavy metals, that are frequently, contained in metal plating wastewater is reported in this paper. The interaction of ionic heavy metals and carbamoyl benzoic acids was studied approaching zeta potential in aqueous solu- tions. These carbamoyl acids are innovative chemicals that demonstrate their potential to bind metallicions as Pb2+, Cu2+ and Hg2+ under specific physicochemical conditions (pH solution and metal–ligand relationship). The amide substituent in each compound induced a specific affinity toward the metallic ions contained in water, and it was studied by measuring zeta potential of an inert surface in contact with the aqueous media. This measurement allowed us to determine the association constants (Kf) with metal ions after defining the stronger interaction between the carbamoyl acids and metallic cations. These results suggest that coagulation-flocculation process could be expected for Pb2+ over all the studied met- als (Cu2+, Hg2+, Ca2+, Fe2+, Ni2+, Mg2+, Ba2+, Al 3+ and Cd2+). The order of effectiveness of the carbamoyl acids for the separation of Pb2+ is b > c > a according to substituent and the calculated values of Kf which match the observed behavior. To corroborate the practical use of carbamoyl acids as coagulants. Sedimentation and clarification kinetics were analyzed with transmittance measurements versus time. Coagulation-flocculation test was validated by SEM-EDS analysis.
Chemical Engineering Journal
Keywords: Carbamoyl acids; Wastewater treatment; Heavy metals; Coagulation-flocculation; Zeta potential